2005
DOI: 10.1021/jp0442403
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Polymers and Carbon Nanotubes:  A Molecular Dynamics Study

Abstract: We used force-field-based molecular dynamics to study the interaction between polymers and carbon nanotubes (CNTs). The intermolecular interaction energy between single-walled carbon nanotubes and polymers was computed, and the morphology of polymers adsorbed to the surface of nanotubes was investigated. Furthermore, the "wrapping" of nanotubes by polymer chains was examined. It was found that the specific monomer structure plays a very important role in determining the strength of interaction between nanotube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
272
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(281 citation statements)
references
References 36 publications
(56 reference statements)
9
272
0
Order By: Relevance
“…As we illustrated before, [20] the contact area of the aromatic rings with the surface is a maximum in this orientation, and thus it achieves the maximum interaction with the CNT. [37] In addition to the vdW attraction and the hydrophobic interaction between the aromatic rings and the surfaces, the p-p stacking is also a key factor that drives the phenyl to this orientation [38,39] and causes the high affinity of the peptide/protein to the CNT. Experimental studies have shown that the peptides with His residues have a higher affinity for CNTs, [15] which could be attributed to the strong interaction between the aromatic rings in His and the CNT surface observed in our simulations.…”
Section: Effective Attraction and Adsorbed Residuesmentioning
confidence: 99%
“…As we illustrated before, [20] the contact area of the aromatic rings with the surface is a maximum in this orientation, and thus it achieves the maximum interaction with the CNT. [37] In addition to the vdW attraction and the hydrophobic interaction between the aromatic rings and the surfaces, the p-p stacking is also a key factor that drives the phenyl to this orientation [38,39] and causes the high affinity of the peptide/protein to the CNT. Experimental studies have shown that the peptides with His residues have a higher affinity for CNTs, [15] which could be attributed to the strong interaction between the aromatic rings in His and the CNT surface observed in our simulations.…”
Section: Effective Attraction and Adsorbed Residuesmentioning
confidence: 99%
“…The following experimental results provided evidence of stress transfer in agreement with the simulation results. Yang et al [29] have studied the interaction between polymers and CNTs using force-field-based MD simulation. They found that the specific monomer structure plays a very important role in determining the strength of interaction between nanotubes and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical studies have addressed this issue using molecular dynamic simulations as well as density functional theory (DFT). [22][23][24][25][26][27][28][29] For instance, the possibility to improve the polymer-CNT alignment by suitable tuning of the temperature, polymer density, and chain length has been demonstrated in Ref. 25.…”
mentioning
confidence: 99%